Effect of Work Ability and Work Motivation on Employee Performance in PT. Lion Mentari Airlines in Makassar - Muhammad Bakri (Patria Artha University, 2018)
This study aims to determine and analyze the influence of work ability on employee performance at PT. Lion Mentari Airlines in Makassar and to know and analyze the influence of work motivation on employee performance at PT. Lion Mentari Airlines in Makassar. The analytical method used in this study is a multiple regression analysis method. Research data was obtained from employees of PT. Lion Mentari Airlines in Makassar. The research approach is an explanatory causal approach. The results showed that based on the results of multiple regression tests, the effect of work ability variables had a positive and significant effect on employee performance at PT. Lion Mentari Airlines in Makassar, meaning that employee performance can be increased if influenced by employee work ability and the influence of work motivation variables have a positive and significant effect on employee performance at PT. Lion Mentari Airlines in Makassar, meaning that employee performance can increase if influenced by employee work motivation.